Supporting bird diversity and ecological function in managed grassland and forest systems needs an integrative approach - Jung, Kirsten; Teuscher, Miriam; Böhm, Stefan; Wells, Konstans; Ayasse, Manfred; Fischer, Markus; Weisser, Wolfgang W.; Renner, Swen C.; Tschapka, Marco (Frontiers in Environmental Science, 2024)
In modified production landscapes biodiversity faces unprecedented pressures from human actions, resulting in dramatic species declines of plant and animal taxa, including birds. Understanding underlying mechanisms responsible for such declines is essential to counteract further loss, and to support practitioners in conserving biodiversity and associated ecosystem function. Here we used standardized bird monitoring data collected over 6 years in managed forest and grassland areas across different regions in Germany, Central Europe. We combined this data with morphometric, ecological, behavioral as well as acoustic trait data and detailed information on local land use management practices to understand how management decisions affect species and functional diversity, as well as ecological processes shaping local species composition. Our results reveal that ecosystem and regional context must be considered to understand how management practices affect bird diversity aspects and composition. In forests regional management decisions related to tree species and stand age affected bird diversity, as well as community and functional composition and indicated environmental sorting due to ecological and behavioral requirements, biotic interactions, and morphometric constraints. In grasslands, independent of local management practices, increased intensity of land use resulted in an overall loss in bird species and functional diversity. Predominantly constraints due to ecological or behavioral requirements affect bird species assemblage composition. In addition, our results indicated the importance of woody vegetation near managed grasslands and indicated the importance of considering environmental conditions beyond the local scale to support bird diversity and associated ecosystem function. Our results highlight that local management decisions, can support bird diversity, and maintain ecological function. However, this needs a view beyond the local scale of management unites. It also demands a joint effort of biologists and land managers to integrate targeted conservation actions into regional management practices and to create a network of habitats within production landscapes to protect nature, guard against biotic and functional homogenization and prevent further degradation of ecosystems in production landscapes.